Using structured problem solving to promote fluid consumption in the prevention of urinary stones with hydration (PUSH) trial - Peter P. Reese; Salima Shah; Emily Funsten; Sandra Amaral; Janet Audrain-McGovern; Kristen Koepsell; Hunter Wessells; Jonathan D. Harper; Rebecca McCune; Charles D. Scales; Ziya Kirkali; Naim M. Maalouf; et al. (BMC Nephrology, 2024)
Abstract Background Structured Problem Solving (SPS) is a patient-centered approach to promoting behavior change that relies on productive collaboration between coaches and participants and reinforces participant autonomy. We aimed to describe the design, implementation, and assessment of SPS in the multicenter Prevention of Urinary Stones with Hydration (PUSH) randomized trial. Methods In the PUSH trial, individuals with a history of urinary stone disease and low urine output were randomized to control versus a multicomponent intervention including SPS that was designed to promote fluid consumption and thereby prevent recurrent stones. We provide details specifically about training and fidelity assessment of the SPS coaches. We report on implementation experiences related to SPS during the initial conduct of the trial. Results With training and fidelity assessment, coaches in the PUSH trial applied SPS to help participants overcome barriers to fluid consumption. In some cases, coaches faced implementation barriers such as variable participant engagement that required tailoring their work with specific participants. The coaches also faced challenges including balancing rapport with problem solving, and role clarity for the coaches. Conclusions We adapted SPS to the setting of kidney stone prevention and overcame challenges in implementation, such as variable patient engagement. Tools from the PUSH trial may be useful to apply to other health behavior change settings in nephrology and other areas of clinical care. Trial registration ClinicalTrials.gov Identifier NCT03244189.